Case report: Complete response after transcatheter arterial chemoembolization combined with donafenib plus tislelizumab therapy for hepatocellular carcinoma with main trunk portal vein tumor thrombus in a patient coinfected with HIV and HBV - Xiao, Xuhua; Fu, Haixiao; Qin, Huixia; Xu, Longkuan; Gu, Jing; Zhang, Zhan; Ya, Houxiang; Jiang, Kaiwen; Jian, Zhiyuan; Li, Shuqun (Frontiers in Immunology, 2024)
Background: Coinfection with the human immunodeficiency virus (HIV) and the hepatitis B virus (HBV) occurs in 5-67% of patients with HIV. HIV weakens the human immune system and leads to various tumors. Patients with unresectable hepatocellular carcinoma (HCC) and HIV experience poor treatment efficacy and have a short survival period. Approximately 70% of cases of HCC are diagnosed at advanced stages due to the subtle onset of the disease. As a result, most cases are not suits for curative therapy.Transcatheter arterial chemoembolization (TACE) is the first-line treatment for intermediate-stage HCC and is commonly used to treat unresectable HCC in China. Recent advancements in systemic treatments have significantly enhanced the effectiveness of unresectable HCC treatment. Several previous study showed that combination treatment combination therapy can enhance the efficacy. Notably, studies proposed that TACE combined targeted drugs with immune checkpoint inhibitors results in a high objective response rate and overall survival. However, the novelty of this study lies in its report of a complete response using a triple combination in patients with HIV and HCC with main trunk portal vein tumor thrombus.Case presentation: A 57-year-old woman was diagnosed with HCC with a main trunk portal vein tumor thrombus combined with HIV infection, cirrhosis, and chronic viral hepatitis. She underwent TACE and was administered donafenib and tislelizumab. This triple therapy treatment regimen resulted in a clinical complete response according to the modified Response Evaluation Criteria in Solid Tumors (mRECIST) based on contrast-enhanced computed tomography.We first used TACE combined with donafenib and tislelizumab for HCC patients with main trunk portal vein tumor thrombus and HIV-HBV coinfection and achieved complete response.